Measurement of a light beam waist - Julca, Franklin (2010)
We have measured both the irradiance distribution and the spatial propagation profiles of a light emitting diode and a HeNe laser using several experimental technique. The experimental value of the waist laser was verified using the ABCD array law at the laser case.